Transient zinc deficiency syndrome in a breast-fed infant due to decreased zinc in breast milk (type II hypozincemia of infancy): A case report and review of the literature - Wei-Li Yang; Chao-Kai Hsu; Sheau-Chiou Chao; Ching-Yuang Huang; Julia Yu-Yun Lee (Wolters Kluwer Medknow Publications, 2012)
Type II hypozincemia of infancy is a rare, hereditary zinc deficiency occurring in infants while exclusively on breast feeding. It is caused by defective transfer of zinc into breast milk. Only a few dozen cases have been reported. A 6-month-old, full-term, breast-fed female infant presented with a 3-week history of erythematous to dusky red papules and annular plaques over the perioral and diaper area as well as the digits. The eruption was accompanied by poor appetite and irritable crying. Serum zinc was low (4.896 μmol/L, normal = 10.71−18.36 μmol/L) in the patient but was normal in the mother. Interestingly, the zinc level in the breast milk was very low (2.142 μmol/L; normal postpartum zinc = 18.36 μmol/L at 6 months). Histopathology of a skin biopsy specimen showed spongiotic psoriasiform dermatitis with pallor of superficial keratinocytes, consistent with deficiency disease. With oral zinc sulfate supplement, her skin lesions improved significantly within 4 days. Type II hypozincemia needs to be differentiated from the classical hereditary acrodermatitis enteropathica, which typically develops symptoms after weaning because of poor intestinal absorption of zinc in the affected infants. Mutations in zinc transporter genes have been detected in SLC39A4 (Zip4) and SLC30A2 (ZnT2), respectively, in classical acrodermatitis enteropathica and type II hypozincemia. No mutation was found in these two genes in the present pedigree. Therefore, the genetic defect in our patient might involve other zinc transporter genes.